(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Promotions have being utilized to impact customer purchasing behaviour for several decades. Adverts aid in the creation of client knowledge and impression of cosmetics items; both of these elements are deadly when it comes to influencing client purchasing behaviour. This study focused on 200 young men and women who use different brands of cosmetics to determine the influence of marketing on their purchase behavior while cultivating awareness and gaining insights. To determine the link among these parameters, linkage and relapsing investigations were used. The findings revealed a new way for managers to create a fair framework for the promotion of restorative goods. These findings reveal that advertisements are quite effective at raising awareness among people, yet they are often overlooked when it comes to gathering genuine information in the minds of purchasers. Because there is a favorable association between these elements, such as shopper attentiveness and buyer cognizance, the consumer will be motivated to acquire a certain item.